Estudo da Estrutura dos Núcleos 17Ne e 13O pela reação de pick-up (3He, 6He) - Guimaraes, Valdir (1994)
The nuclear structme of 17Ne and 13O has been studied by the 20Ne(3He,6He)17Ne and 16O(3He,6He)13O reactions at 70 MeV and 80 MeV, respectively. Fifteen levels were identified, and angular distributions have been measured for nine of these levels in 17Ne, while for 13O eighteen levels were identified, but angular distributions were obtained for only ten levels. The observed transferred angular momentum dependence of these angular distributions allowed spin-parity assignments. The T= 3/2 quartet analog states in mass A=17 have been completed for six levels. The results of the isobaric multiplet mass equation analysis show a slight linear dependence of the b and c coefficients on the excitation energy. It was found that the coefficients for the positive parity states do not follow the systematics of the negative parity states. The absolute values of the b and c coefficients are larger for the positive parity states. An analysis in terms of Coulomb energy displacement indicates a possible configuration mixing or core polarization effect in these states. The d coefficient also has a large deviation from zero, only for the positive parity states indicating a possible expansion of the radial wavefunction or some isospin symmetry breaking effects. Further detailed theoretical interpretation of these effects may bring valuable information about the configuration and structure of these states. The leveis in 13O were measured with good energy resolution, and thus, it was possible to identify the first excited state unambiguously. However, if one identifies this state as the analog of the known first excited state in the mirror nucleus 13B, this leads to one of the largest level shifts known in literature.